The chromosomal basis of cancer - Duesberg, Peter; Li, Ruhong; Fabarius, Alice; Hehlmann, Rüdiger (Cellular oncology, 2005)
Conventional genetic theories have failed to explain why cancer (1) is not heritable and thus extremely rare in newborns, (2) is caused by non-mutagenic carcinogens, (3) develops only years to decades after initiation by carcinogens, (4) follows pre-neoplastic aneuploidy, (5) is aneuploid, (6) is chromosomally and phenotypically “unstable”, (7) carries specific aneusomies, (8) generates much more complex phenotypes than conventional mutation such as multidrug resistance, (9) generates nonselective phenotypes such as metastasis (no benefit at native site) and “immortality” (not necessary for tumorigenesis), and (10) does not contain carcinogenic mutations. We propose, instead, that cancer is a chromosomal disease. Accordingly carcinogenesis is initiated by random aneuploidies, which are induced by carcinogens or spontaneously. Since aneuploidy unbalances 1000s of genes, it corrupts teams of proteins that segregate, synthesize and repair chromosomes. Aneuploidy is therefore a steady source of chromosomal variations from which, in classical Darwinian terms, selection encourages the evolution and malignant progression of cancer cells. The rates of specific chromosomal variations can exceed conventional mutations by 4-11 orders of magnitude, depending on the degrees of aneuploidy. Based on their chromosomal constitution cancer cells are new cell “species” with specific aneusomies, but unstable karyotypes. The cancer-specific aneusomies generate complex, malignant phenotypes through the abnormal dosages of 1000s of genes, just as trisomy 21 generates Down syndrome. In sum, cancer is caused by chromosomal disorganization, which increases karyotypic entropy. Thus, cancer is a chromosomal rather than a genetic disease. The chromosomal theory explains (1) non-heritable cancer because aneuploidy is not heritable, (2) non-mutagenic carcinogens as aneuploidogens, (3) long neoplastic latencies by the low probability of evolving new species, (4) nonselective phenotypes via genes hitchhiking with selective chromosomes, and (5) immortality because, through their cellular heterogeneity, cancers survive negative mutations and cytotoxic drugs via resistant subspecies.